2015
DOI: 10.1136/bmjopen-2015-007819
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study using MRI to measure depths of acupuncture points in neck and shoulder region

Abstract: ObjectivesThere are safety issues associated with acupuncture treatment. Previous studies regarding needling depth of acupuncture points revealed inconsistent results due to vague depth definition, acupuncture point localisation and measuring tools. The objective of this study is to find and compare the differences of the mean depths of 11 acupuncture points in the neck and shoulder region between subjects, with variables including gender and body mass index (BMI).SettingThis study was conducted at a single me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
1
11
0
1
Order By: Relevance
“…GB21 is an acupoint near the lung apex and Lee et al [13] reported the distance from the surface of the skin to the thoracic cavity between 3.4 cm and 3.9 cm. Chou et al [14] proposed the safe depth of needling GB21 according to gender and BMI. Depths of 4.0 cm (3.7-3.9 cm) for male underweight patients, 5.3 cm (5.1-5.6cm) for normal-weight patients, 6.4 cm (6.0-6.7 cm) for overweight patients, and 7.1 cm (6.8-7.5 cm) for obese patients were proposed.…”
Section: Discussionmentioning
confidence: 99%
“…GB21 is an acupoint near the lung apex and Lee et al [13] reported the distance from the surface of the skin to the thoracic cavity between 3.4 cm and 3.9 cm. Chou et al [14] proposed the safe depth of needling GB21 according to gender and BMI. Depths of 4.0 cm (3.7-3.9 cm) for male underweight patients, 5.3 cm (5.1-5.6cm) for normal-weight patients, 6.4 cm (6.0-6.7 cm) for overweight patients, and 7.1 cm (6.8-7.5 cm) for obese patients were proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Among previous studies on the safe needling depth at GB21, four were carried out using cadavers [ 11 , 12 , 16 , 17 ], one using MRI [ 14 ], one using CT [ 13 ], and one using ultrasonography [ 18 ]. However, only two of these studies focused solely on GB21, and these were both carried out using cadavers [ 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many researchers have tried to determine the safe needling depth or the risk depth at GB21. However, to date, studies have only been conducted using cadavers [ 11 , 12 ] or CT [ 13 ] and MRI [ 14 ] analyses. Such studies are limited by factors such as cadaveric rigidity, as well as limited postural variation (i.e., supine position only) and the risk of radiation exposure during CT.…”
Section: Introductionmentioning
confidence: 99%
“…Among the major acupuncture-related adverse events, pneumothorax is the most severe, and therefore it is crucial that acupuncture practitioners identify safe depths of insertion of acupuncture needles for individual patients. Studies by Professor Lin and colleagues have extensively investigated the safe needle depth [8][9][10][11][12]. In one study of 11 acupuncture points in the neck and shoulder region, they found that the mean depths for the points around the shoulder in all study subjects, regardless of BMI and gender, were as follows: GB21 = 5.6 cm, SI14 = 5.2 cm, and SI15 = 8.8 cm.…”
Section: Introductionmentioning
confidence: 99%